2008
DOI: 10.1002/art.24141
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of molecular imprints in the antigen‐experienced B cell repertoire by rituximab

Abstract: Objective. Transient B cell depletion by rituximab has recently gained more importance in the treatment of rheumatic disorders. Nevertheless, little is known about the reemerging B cells. We analyzed dynamic changes in the repopulating B cells, particularly the postswitch B cells, and studied the mutational patterns of Ig genes in antigen-experienced B cells.Methods. Five patients with active rheumatoid arthritis (RA) were treated with rituximab. In 3 patients, B cell receptor (BCR) gene analysis was performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 47 publications
0
16
0
Order By: Relevance
“…Previous work in our laboratory provided evidence of an impact on molecular imprints shaping the Ig repertoire with similar mutational targeting of all V H gene families (V H 1-V H 6) (29). Changes in the pattern of somatic hypermutation after temporal B cell depletion by rituximab have also been observed (32).…”
Section: Discussionmentioning
confidence: 96%
“…Previous work in our laboratory provided evidence of an impact on molecular imprints shaping the Ig repertoire with similar mutational targeting of all V H gene families (V H 1-V H 6) (29). Changes in the pattern of somatic hypermutation after temporal B cell depletion by rituximab have also been observed (32).…”
Section: Discussionmentioning
confidence: 96%
“…Open-label studies in RA have shown that the presence of B cell subsets during depletion or repletion may be a predictor of reduced response or early relapse 8386. Indeed, a lack of complete depletion of plasma B cells after an initial infusion with rituximab was associated with a poorer response than for patients in whom depletion was complete 83 87.…”
Section: Cellular Biomarkersmentioning
confidence: 99%
“…We have also found that B cell depletion may alter lymphoid architecture by eliminating LTα bearing and TNF secreting B cells, resulting in a prolonged delay in memory B cell reconstitution that correlates with clinical response in SLE [54]. Such mechanisms may explain the delayed acquisition of mutations in the memory B cell compartment after rituximab [55,56]. …”
Section: New Insights Into B Cell Depletion In Ramentioning
confidence: 99%